The Moderating Influence of Brand Image on the Relationship Between Customer Engagement and Customer Loyalty - Quynh, Ngo Hai (Indian Journal of Marketing, 2019)
The current study attempted to address the role of customer engagement (CE) in the relationship with other psychological constructs leading to supply a new higher-order model of CE that can explain the nature of CE upon the reviews of literature. Therefore, the discovery of the importance of CE was carried out in the Vietnamese restaurant service context. I found that service quality and perceived value were important causes leading to more engagement. Moreover, the influence of CE on perceived value was the strongest and the relationship between CE and service quality was the weakest. Also, the influence of CE on customer loyalty for the lower-income customers was higher than that for higher-income ones ; also, the income of the customers did not moderate the relationships between perceived value/service quality and CE. The relationship between CE and customer loyalty was weakened by the moderating influence of brand image. Thus, a crucial contribution of the current research is to give knowledge of CE by investigating the diverse nature of the relationships among order-high marketing structures and CE in a comprehensive integrated model.